2014
DOI: 10.1007/s12350-014-9896-2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular implantable electronic device infection: delayed vs standard FDG PET-CT imaging

Abstract: Delayed FDG PET-CT imaging should be considered at least in patients with negative 1-hour scan and founded suspicion of pacing lead infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 28 publications
1
75
0
2
Order By: Relevance
“…Contemporary studies have optimized patient preparation through use of dietary carbohydrate restriction, thereby reducing physiological myocardial 18 F-FDG uptake, making it easier to identify pathological uptake. [20][21][22][23][24][25] The current meta-analysis examined a subgroup of studies that utilized appropriate dietary preparation (?/-heparin) and show that the sensitivity of 18 F-FDG PET/CT for detecting CIED infection was substantially increased (to 92%) using this strategy. 15 This development represents a milestone in the advancement of metabolic imaging of cardiovascular infection and has possibly contributed to increasing clinician confidence in reporting on the extent of intracardiac extension of infection.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Contemporary studies have optimized patient preparation through use of dietary carbohydrate restriction, thereby reducing physiological myocardial 18 F-FDG uptake, making it easier to identify pathological uptake. [20][21][22][23][24][25] The current meta-analysis examined a subgroup of studies that utilized appropriate dietary preparation (?/-heparin) and show that the sensitivity of 18 F-FDG PET/CT for detecting CIED infection was substantially increased (to 92%) using this strategy. 15 This development represents a milestone in the advancement of metabolic imaging of cardiovascular infection and has possibly contributed to increasing clinician confidence in reporting on the extent of intracardiac extension of infection.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Conversely, the late image acquisition assumes a persistent glucose influx in inflammatory activated cells and further clearance of glucose or FDG from the blood pool yielding a higher contrast between activity in infected regions and background. 2 Previous investigations 2,3 have indeed suggested late imaging to add diagnostic value in the identification of infected cardiovascular implants. As the authors point out, the case description reported by Caldarella 2 are in agreement with the one false-positive finding in the current investigation on late imaging.…”
Section: See Related Article Pp 1960-1967mentioning
confidence: 99%
“…cardiac implantable electronic device lead infection may reflect a different inflammatory disease entity for which late image acquisition in fact appear to be more suitable. [3][4][5] As regards the quantification of the FDG uptake, maximal standard unit value (SUV max) and target-to-background ratio (TBR) between standard and late image acquisition unraveled a great variability in the individual measurements resulting in a wide overlap between both groups with PVE and non-PVE. 1 Such finding emphasizes that even uninfected PHVs may have a certain amount of sterile inflammation, reflecting post-surgical tissue response and/or a mild foreign body reaction depending on the post-interventional period.…”
Section: See Related Article Pp 1960-1967mentioning
confidence: 99%
“…However, the use of antimicrobial should be taken into account during imaging interpretation since they might affect the intensity of FDG uptake due to their immunomodulatory effect [7]. Late PET/CT imaging (2-3 h after FDG injection) should be considered in patients when negative 1-h PET/Ct scan in maximizing the contrast between septic foci and background [33].…”
Section: Limitations and Technical Considerationsmentioning
confidence: 99%